Khartoum Structure Plan’s Strategies: A Review of Sustainability, Action and Prospects - Awad Hafazalla, Abdulhafeez (University of Khartoum Engineering Journal, 2022)
Khartoum, the capital city of Sudan, is experiencing severe planning problems including the lack of adequate levels of services, infrastructure, public transport, housing problems, environmental degradation and faintness of development controls. Four development plans were previously adopted since 1910, most of which were not adequately implemented as planned due to the absence of government’s will, inadequate financial resources, and inadequate and unrealistic programs. A fifth structure plan has been prepared and adopted in 2009 for the next 25 years. The paper discusses the conformity of the plan proposal with sustainable development measures regarding five aspects that relate to the plan solutions viz., the methodology, development strategies, transportation, infrastructure, and development controls in order to avoid the destiny of the former plans that were unsatisfactorily implemented. The paper, applying deductive and comparative research methods, questioned the validity and sustainability of the plan’s outcome such as creating nine new satellite towns to accommodate six million people for such an already sprawled city. The paper also highlighted some locational and land use planning problems of urban activities that also question the issue of sustainability.